The Lomidine files : the untold story of a medical disaster in colonial Africa - Lachenal, Guillaume, 1978- (Johns Hopkins University Press, 2017)
Ultimately, it illuminates public health not only as a showcase of colonial humanism and a tool of control but as an arena of mediocrity, powerlessness, and stupidity.